PENGARUH KOMPOSISI SILIKON DAN TEMPERATUR TUANG TERHADAP KERENTANAN HOT TEARING PADA Al-Si DENGAN CETAKAN CONSTRAIN ROD CASTING MODIFED HORIZONTAL - , AKHYAR,ST, Dr. Suyitno, S.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Hot tearing is a casting defect that occurs on surface and subsurface in the casting products. Solidification causes thermal contraction and shrinkage in the liquid metal, and liquid metal restrained by mold design then hot tearing will be occur. The purpose on this study is to determine the effect of silicon composition and pouring temperature on hot tearing susceptibility, by observed cooling curve, macro and micro structure, SEM, and hardness of Al-Si alloys. Alloying aluminum base with ADC12 as addition to get four variations of silicon composition have been done in this study, there were 0.24%Si, 1.19%Si, 1.66%Si, and 2.6%Si. Pouring temperature that used were 710 oC, 760 oC and 810 oC, and constant mold temperature at 220 oC. The method used was visual method with constrained rod casting mold modified (CRCM) horizontal mold. Hot tearing increases with increasing silicon composition until reaches maximum at 1.19% with pouring temperature 760 Â°C (45 HTS), then hot tearing decreases with the addition of the silicon composition. Cooling curve shows the temperature of liquid metal drops from 710 oC to 250 oC at 25 seconds when liquid metal poured into CRCM horizontal mold, then the temperature cooling down slowly until reaches room temperature for about 6 hours. Macro structures and SEM indicate that hot tearing is formed over a range of ductile, semi-solid, and when the liquid metal slurry, it can be seen from the dendrites. Microstructure shows that distribution of silicon segregation in aluminum matrix increased with increasing silicon composition in Al-Si alloys from 0.24% to 2.6%. Hardness increases with increasing silicon composition and reaches maximum at 2.66% silicon composition with pouring temperature 810 oC (62.83 BHN).